Pembangunan dan penilaian modul pengajaran dan pembelajaran menggunakan kalkulator grafik dalam pembelajaran persamaan kuadratik - Basiran, Haspiah (2006)
Teaching and learning are processes carried out to achieve a goal in the educational system. Thus, plannings need to be prepared in order to accomplish them. The research was carried out to develop and evaluate the effectiveness of the modules which utilize Graphic Calculator as the Teaching and Learning Environment (also known as The Modules of Teaching and Learning Utilizing Graphic Calculator or with the acronym of MPPBKG in Bahasa Melayu) in the teaching of Quadratic Equation learning. The study was carried out in three phases. Phase One involved the preparation of six modules consisting of Teaching and Learning Worksheet Activity based on the constructivism learning model as outlined by the Curriculum Development Center of The Ministry of Education. The preparation of these modules also was based on the optimized exploitation towards the exploratory environment and visualization which is built-in in the Graphic Calculator. Phase Two involved the implementation of MPPBKG in a classroom consisting of 30 students learning the topic of Quadratic Equation. Phase Three touched on the research into the effectiveness of the MPPBKG which was studied from three perspectives related entirely to the topic being researched on namely a) the effectiveness in assisting students to increase their concept understanding b) the effectiveness in assisting students to master the skill of problem solving c) the perception and readiness of students towards the utilization of MPPBKG as a Teaching and Learning environment which is student - centered. When Phase Two was carried out, that was during the MPPBKG practice, it involved the collection of quantitative and qualitative data which were recorded through the test of Quadratic Equation topic (pre and post), the students’ written work in the usage of Worksheets Activity, interviews and questionnaires. The Quantitative data was analyzed basing on the simple statistics involving percentages index, mean score, bi-lateral frequency timetable and t test (paired sample). As for the Qualitative data, it was analyzed focusing on the level and the nature of a sample who practiced the Teaching and Learning activity as suggested in MPPBKG. The outcomes of the analysis on various data in Phase Three show that MPPBKG applied did help in assisting students to increase their concept understanding and their problem-solving skill of the topic researched on. This was concluded based on the comparison of achievement graphs in every part of learning outcomes; the increase of 83% in Part A, 86% in Part B and 79% in Part C from the overall sample which was substantiated by the significant t test (paired sample) in every part. Overall, the students responded positively towards the MPPBKG application and were ready to practice it as one of the learning environment approached other than the conventional way of learning.